Assessment of antibiotic resistance profile of bacteria isolated from Ghaghara River, India. Issue 11 (21st October 2022) - Ravi, Nirdesh Kumar; Pal, Arun Kumar; Soni, Ramendra; Tripathi, Pooja; Singhal, Anjali; Jha, Pawan Kumar; Tripathi, Vijay
Abstract: Excessive anthropogenic activities play a significant role in the emergence and dissemination of antibiotic resistance in urban streams and river sediment. The objectives of the present study were to investigate the antibiotic susceptibility profile, molecular detection of antibiotic resistance genes (ARGs), and identification of multidrug-resistant bacterial isolates in the mainstream and tributaries of the Ghaghara River. The obtained data indicated that the majority of the isolates were identified as Bacillus spp. (40%) followed by Klebsiella quasipneumoniae (20%), Exiguobacterium undae (13.33%). Most of the bacterial isolates were resistant against penicillin G (P) (24%), cefuroxime (CXM) (20%), amoxicillin (AMX) (18%), and ampicillin (AMP) (17%) in sediments samples, whereas penicillin G (27%), cefuroxime (CXM) and erythromycin (E) was 13%, AMP and cefaclor both showed 12% in water samples respectively. This study provides insight into the prevalence of multiple antibiotic-resistant bacterial diversity in the Ghaghara River and provides the route to disseminate the multidrug-resistant pathogens in the human and animal population through the aquatic environment. HIGHLIGHTS: 16S rRNA analysis for bacterial identification and microbial study. MDR bacterial community in water and sediment of Ghaghara River. Bacillus species bacteria are dominant in multidrug resistance nature. Penicillin and cefuroxime antibiotics showing resistance against most of bacteria. ARGs like blaKPC, blaNDM, and aminoglycoside (ant3″) are dominant in all water and sediment samples. Graphical Abstract